Pompe’s Disease in Infancy: A Case Report (GAIMS Journal of Medical Sciences, 2024)
Glycogen storage disorders (GSDs) are inherited metabolic disorders characterized by defects in glycogen metabolism, leading to abnormal glycogen accumulation in various tissues. Pompe’s disease, a severe form of GSD, results from a deficiency in the enzyme acid alpha-glucosidase (GAA), causing lysosomal glycogen accumulation, primarily affecting cardiac and skeletal muscles. This case study presents a 45-day-old female infant with Pompe’s disease, initially presenting with fever, cough, cold, and respiratory distress. Clinical assessment revealed tachypnoea, elevated heart rate, hypotension, hepatosplenomegaly, elevated liver enzymes, and metabolic acidosis. Diagnostic tests confirmed Pompe’s disease through low alpha-glucosidase activity. Despite initiating antibiotic treatment and ventilatory support, the patient’s condition worsened, necessitating re-intubation. Pompe’s disease presents a broad spectrum of clinical manifestations, with early diagnosis and intervention being crucial for managing the infantile form. Enzyme replacement therapy (ERT) with recombinant human GAA has markedly improved patient outcomes, yet challenges remain, including variability in treatment response and the high cost of therapy. Ongoing research focuses on novel therapeutic approaches and enhancing patient care. This case underscores the importance of early recognition and comprehensive management to improve prognosis in Pompe’s disease.